A Giant Atypical Neurofibroma in the Right Thoracic Cavity of a 57-Year-Old Man: A Case Report with Review of the Literature - Guo, MD, PhD, Rongjun; Chen, MD, PhD, Frank; Heffner, MD, Reid (North American Journal of Medicine and Science, 2009)
Intrathoracic neurogenic tumors are not uncommon, but presentation as a giant mass in the thoracic cavity is rare. Although several cases of intrathoracic giant malignant peripheral nerve sheath tumor have been reported, only one case of intrathoracic giant benign neurofibroma appears in the literature. In this report, we describe a very rare case of atypical giant neurofibroma in the right thoracic cavity. The patient was a 57 year old African American man, who developed sudden cardiac arrest and passed away in the emergency room. At autopsy, a huge encapsulated firm tumor was found in the right thoracic cavity, attached to the vertebral bodies and superficially adherent to the upper and middle lobes of the right lung. This giant mass weighed 2140 grams and measured 31 x 30 x 5.5 cm. Microscopically, the tumor consisted of interweaving fascicles of spindle cells with scattered atypical nuclei. Immunohistochemical studies showed that tumor cells were focally positive for S100, and negative for SMA, desmin, calretinin, Pan CK, CK5/6, EMA, CD99, CD34 and p53. The overall morphological and immunohistochemical features were diagnostic of an atypical neurofibroma.